Konsepsi dan Strategi Muhammad SAW dalam Mendirikan Negara Madinah Al-Munawwarah - Vachruddin, Vrisko Putra (Universitas Hamzanwadi, 2021)
Under increasingly bold and severe pressure by the Quraysh infidels in the city of Makkah, the revelation of God came down that ordered the Prophet and the Muslims of Mecca to emigrate to the city of Yastrib (Medina). The migration of Prophet Muhammad SAW to the city of Yastrib brought a great influence on the unity of all communities in the city of Yastrib with the establishment of a pluralist state. The Prophet's role as a religious leader and political leader chosen based on consensus deliberations could was able to create a social community in the heterogeneous society so that social solidarity emerged assuming on the basis of one city. This article aims to explain the conception and strategy of Muhammad in uniting the people of Medina so that the pluralist state stands. This research uses historical methods by going through stages, namely; heuristics, source criticism, interpretation and historiography. The prophet's basic conception and strategy in establishing are state of Medina is by: establishing mosques, brotherhood of the Muhajirin and Ansar, cooperation between the components of the population of Medina (Muslim and Non-Muslim), laying political, economic, and social foundations for new communities and renaming the city.Dibawah tekanan yang semakin berani dan berat oleh kaum kafir Quraisy di kota Makkah, maka turunlah wahyu Tuhan yang memerintahkan Nabi dan orang-orang Islam Mekkah untuk hijrah ke kota Yastrib (Madinah). Hijrahnya Nabi Muhammad SAW ke kota Yastrib membawa pengaruh besar terhadap bersatunya seluruh komunitas yang berada di kota Yastrib dengan berdirinya Negara yang berkonteks pluralis. Peran Nabi sebagai pemimpin agama dan pemimpin politik yang dipilih berdasarkan musyawarah mufakat mampu menciptakan komunitas sosial dalam masyarakat heterogen tersebut sehingga muncul sikap solidaritas sosial atas dasar satu kota. Artikel ini bertujuan untuk menjelaskan tentang konsepsi dan strategi Muhammad dalam menyatukan masyarakat Madinah sehingga berdirilah Negara yang berkonteks pluralis. Penelitian ini menggunakan metode sejarah dengan melalui tahapan yaitu; heuristik, kritik sumber, interpretasi dan historiografi. Konsepsi dan strategi dasar Nabi dalam mendirikan negara Madinah ialah dengan cara mendirikan masjid, mempersaudarakan kaum Muhajirin dan Anshar, kerjasama antar komponen penduduk Madinah (Muslim dan Non muslim), meletakkan dasar-dasar politik, ekonomi, dan sosial untuk masyarakat baru serta pergantian nama kota.